Digital Transformation: Creating An Effective And Efficient Court In Indonesia - Indriati Amarini; Yusuf Saefudin; Ika Ariani Kartini; Marsitiningsih; Noorfajri Ismail (Universitas Muhammadiyah Malang, 2024)
LEGALITY: JURNAL ILMIAH HUKUM Volume 31 Issue 2 Page (266-284)